Levulinic acid : a sustainable platform chemical for value-added products /: a sustainable platform chemical for value-added products. (2022) - Lima, Ana Lúcia de; Mota, Claudio J. A; Fernandes, Daniella R; Pinto, Bianca Peres
No abstract available